Synthesis of new enantiopure poly(hydroxy)aminooxepanes as building blocks for multivalent carbohydrate mimetics - Bouché, Léa; Kandziora, Maja; Reissig, Hans-Ulrich (Beilstein Journal of Organic Chemistry, 2014)
New compounds with carbohydrate-similar structure (carbohydrate mimetics) are presented in this article. Starting from enantiopure nitrones and lithiated TMSE-allene we prepared three 1,2-oxazine derivatives which underwent a highly stereoselective Lewis acid-induced rearrangement to give bicyclic products in good yield. Subsequent reductive transformations delivered a library of new poly(hydroxy)aminooxepane derivatives. The crucial final palladium-catalyzed hydrogenolysis of the 1,2-oxazine moiety was optimized resulting in a reasonably efficient approach to a series of new seven-membered carbohydrate mimetics.
Keywords: aminooxepanes; carbohydrate mimetics; hydrogenolyses; Lewis acid-induced; lithiated allenes; nitrones; 1,2-oxazines; rearrangements; reductions